MULTI-FIELD STABILIZED FINITE ELEMENT APPROXIMATIONS FOR OLDROYD-B FLUID FLOWS - dos Santos, D. D.; Frey, S.; Naccache, M. F.; Mendes, P. R. de Souza (Revista de Engenharia Térmica, 2013)
This work concerns with numerical simulations of creeping and inertial flows of viscoelastic fluids. The mechanical model consists of mass and momentum balance equations, coupled with the Oldroyd-B fluid. The model is approximated by a multi-field Galerkin least-squares (GLS) methodology in terms of extra-stress, velocity and pressure. The GLS method, introduced by Hughes et al. (1986) in the context of the Stokes problem for Newtonian fluid flows, allows the use of combinations of equal-order finite element interpolations and remains stable even for elastic- and inertiadominated fluid flows. Some steady simulations of Oldroyd-B fluids, flowing over a slot, are herein carried out. The influence of inertia and fluid viscoelasticity is taken into account ranging the Reynolds and Weissenberg numbers for relevant values of this flow. The results are in accordance to the viscoelastic literature and reassure the fine stability features of the GLS formulation.